Satisfaction of family members with inpatient psychiatric care and its correlates: a national survey in China - Jiang, Feng (BMC Psychiatry, 2019)
BACKGROUND: Measuring family members’ satisfaction with inpatient psychiatric care may help improve the quality of healthcare in psychiatric hospitals. This survey aimed to investigate the satisfaction of family members with inpatient psychiatric care and to explore its associated factors, using a newly-developed 5-item questionnaire. METHODS: This study included 1598 family members of psychiatric inpatients in 32 tertiary public psychiatric hospitals in 29 provinces of China. Satisfaction and demographic data were collected by research staff while patient and hospital data were retrieved separately. RESULTS: We found that the overall satisfaction level was 93.84% (23.46/25). The total satisfaction score in Northeast China was the highest, followed by the East, Middle and West regions (p < 0.001). There was no significant sex difference in total family satisfaction scores. Family members with a lower educational background (elementary school or less) had significantly lower satisfaction. Family members of patients who were diagnosed with schizophrenia were significantly less satisfied with doctor-family communication. In different treatment response subgroups, the marked improvement subgroup had significantly higher total satisfaction scores and subscores. Meanwhile, lower self-payment expenses and a higher number of psychologic treatments offered per day were significantly associated with higher total satisfaction scores and all subscores. Logistic regression showed a higher educational background, more psychologic treatments offered per day, adequacy of professional staffing (higher doctor/bed, nurse/bed and psychologist/bed ratio) were all significantly associated with higher family satisfaction. CONCLUSIONS: We suggest government and hospital managers recruit more mental health professions to improve family satisfaction. If feasible, providing more psychologic treatments to inpatients may also improve families’ satisfaction and involvement.